Tremor-Dominant in Parkinson Disease: The Relevance to Iron Metabolism and Inflammation - Lian, Teng-Hong; Guo, Peng; Zuo, Li-Jun; Hu, Yang; Yu, Shu-Yang; Yu, Qiu-Jin; Jin, Zhao; Wang, Rui-Dan; Li, Li-Xia; Zhang, Wei (Frontiers in Neuroscience, 2019)
Background: Tremor is one of the most predominant symptoms of patients with Parkinson disease (PD), but the underlying mechanisms for tremor relating to iron and its metabolism-related proteins and the inflammatory factors in cerebrospinal fluid (CSF) and serum have not been fully elucidated. Methods: A total of 135 PD patients were divided into a tremor-dominant (PD-TD) group (N = 74) and a postural instability and gait difficulty-dominant (PD-PIGD) group (N = 39) based on the ratio of mean tremor score to the mean bradykinesia/rigid score of the Unified Parkinson’s Disease Rating Scale (UPDRS) III. Age and sex-matched healthy controls were recruited (N = 35). Demographic variables were evaluated; iron and its metabolism-related proteins and the inflammatory mediators in both CSF and serum were measured in these groups. The relevance of iron metabolism, inflammation and PD-TD were analyzed. Results: (1) The PD-TD group had significantly decreased L-ferritin, increased iron levels in CSF and increased ferritin levels in the serum compared with the PD-PIGD and control groups (P < 0.05). (2) The PD-TD group had significantly enhanced IL-6 levels in both CSF and serum compared with the PD-PIGD and control groups (P < 0.05). (3) In CSF, the IL-6 level was increased as the iron level was elevated in the PD-TD group (r = 0.308, P = 0.022). In serum, the IL-6 level was increased as the ferritin level was elevated in the PD-TD group (r = 0.410, P = 0.004). Conclusion: The interplay between disturbed iron metabolism and relevant inflammation might modulate clinical phenotypes of PD.